Gaussian white noise stimulation as an alternative method to excite sensory neurons - Losgott, Thomas; Schicker, Klaus W.; Hilber, Karlheinz; Boehm, Stefan; Salzer, Isabella (Frontiers in Pharmacology, 2025)
IntroductionPeripheral nerve endings of dorsal root ganglion (DRG) neurons act as nociceptors and generate action potentials in response to noxious stimuli. Primary cultures of dissociated DRG have been used extensively to study changes neuronal excitability caused by either analgesics or pathological conditions, such as inflammation. The dissociation procedure can be viewed as a form of axotomy, and one might expect a resulting increase in excitability of the neurons during the subsequent culture period. However, changes in firing properties of DRG neurons over time in vitro have not been investigated systematically.Methods Thus, the current experiments compared action potential firing in dissociated DRG neurons after one to 7 days in culture and examined Gaussian white noise as novel stimulation paradigm. Primary cultures of DRG neurons were recorded in perforated patch current-clamp. Action potentials were evoked either by a sequence of five rectangular current pulses with increasing amplitudes or by Gaussian white noise of varying RMS amplitudes and frequencies.Results Conventional rectangular current injections triggered 19 ± 20 action potentials in cells when recorded within 24 h after dissociation. After 7 days in culture, DRG neurons fired 4.3 ± 0.7 action potentials in response to current pulses. Inflammatory mediators increased numbers of action potentials evoked by rectangular current pulses within 24 h after dissociation to 66 ± 54, but left those elicited after 7 days in vitro unaltered (4.3 ± 0.5). In the same set of neurons kept in culture for 7 days, Gaussian white noise stimuli triggered 1,540 ± 470 action potentials, and this number was increased to 2089 ± 685 by inflammatory mediators. The Kv7 channel activator retigabine and the paracetamol metabolite n-acetyl-p-benzoquinone imine (NAPQI) decreased numbers of action potentials triggered by Gaussian white noise, but failed to do so when rectangular current pulses were used as stimuli, both in neurons after 7 days in culture.Discussion These results demonstrate a decrease in the excitability of DRG neurons from day one to 7 after dissociation and reveal Gaussian white noise as reliable trigger of action potential firing in these neurons.